The Effect of Rare Earth (RE) Metal Doping of Zno, On Magnetic and Optical Properties of Zno Crystals Structure - Gizachew Diga Milki (International Journal of Crystalline Materials, 2025)
The magnetic and optical properties of magnetic semiconductors relays on the crystal structure, type and amount of dopant ions, and particle size. Then, the effect of rare earth metal (Dy, Eu, and La) doping on crystal structures, magnetic properties and optical properties are seen. It is revealed that the optical band gap of ZnO decrease down from 3.37eV up on doping with RE metals. Then, the Hamiltonian of the system is determined by using the Heisenberg’s and Greens theorem. The exchange integral is determined by 3D Heisenberg model while electronic states are calculated by the Green’s theorem. The expected magnetism is due to defect states, quantum size effect and double exchange mechanism. For the ferromagnetic states, the exchange integral is positive while it is negative for the antiferromagnetic states. Retarded Green’s theorem revealed that both Magnetic and optical properties of RE doped ZnO are interdependent phenomenon. The combined effect of magnetic and optical properties of RE: ZnO exhibit can be tailored for biomedical and bioelectronics’ applications. Furthermore, the incorporation of rare earth (RE) ions such as Dy, Eu, and La into the ZnO lattice introduces localized magnetic moments that interact with the charge carriers of the host semiconductor, leading to enhanced spin polarization and modified electronic transitions. These dopant ions create defect sites, oxygen vacancies, and lattice distortions, which play a crucial role in tuning the magnetic and optical responses of the material. The reduction in band gap energy upon doping can be attributed to the formation of intermediate energy levels within the forbidden band, facilitating visible light absorption and improving photocatalytic efficiency. The interaction between the 4f electrons of RE ions and the 3d electrons of Zn²⁺ ions enhances the ferromagnetic coupling through exchange interactions.
Keywords: Exchange integral; double exchange; ferromagnetism; magnetic semiconductor; quantum size effect; spin interaction